The correlation between occurrence of dental caries and oral health-related quality of life (OHRQoL) of elderly population in Yogyakarta Special Region - Dewi Agustina; L Hanindriyo; E Widita; R Widyaningrum (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Dental caries is the most common oral disease affecting humans. Based on the Indonesia Basic Health Research (Riskesdas) 2013, prevalence of dental caries in 2013 increased up to 53.2% from 43.4% in 2007. One of the two most increasing prevalence occurred in population of more than 65 years. This disease might affect oral health-related quality of life (OHRQoL) since it causes pain, physical and psychological discomfort. The aim of the study was to evaluate the correlation between occurrence of dental caries and OHRQoL in elderly population in Yogyakarta Special Region. One hundred and eighteen people aged 60 – 80 years consisting 73 female and 45 male involved in the study. The occurrence of dental caries and OHRQoL were determined using decay-missing-filling teeth (DMFT) index, whereas geriatric oral health assessment index (GOHAI) instruments, respectively. The data then were classified into very low, low, moderate and high DMFT and low, moderate and high GOHAI. Spearman’s rank correlation test was conducted to determine correlation between occurrence of dental caries and OHRQoL. Mean scores ofDMFT index and GOHAI were 16.61 ± 7.16 and 47.97 ± 9.03, respectively. Very low, low, moderate, and high DMFT index were experienced by 4 (3.38%), 13 (11.02%), 25 (21.19%) and 76 (64.41%) of 118 elderly, respectively. Low, moderate and high GOHAI were experienced by 71 (60.17%), 25 (21.19%) and 22 (18.64%) of 118 elderly, respectively. Spearman’s rank correlation test showed that the correlation coefficient (r) was -0.263 (p=0.004). There is a negative moderate significant correlation between the occurrence of dental caries and OHRQoL of elderly population in Yogyakarta Special Region.